Majalah “Galang Kangin” sebagai Media Penyampaian Nilai Bagi Jemaat Gereja Kristen Protestan di Bali (GKPB) Wilayah Kota Denpasar - Merry S, Claudiya; Alit Suryawati, I Gusti Agung; Pascarani, Ni Nyoman Dewi (E-Jurnal Medium, 2017)
The use of internal magazines in an organization, often published by a public relations department (PR) of a corporation nature. This is in contrast to the religious organization of the Gereja Kristen Protestan di Bali (GKPB) which does not have a PR department, but performs a PR function by publishing an internal magazine as a medium for disseminating value. This study aims to find out how the magazine Galang Kangin role as a medium for delivering value for GKPB congregation in the city of Denpasar. This research uses descriptive qualitative method with data collection technique using interview technique, observation and documentation study. Techniques of determining informants by way of purposive and snowball. Informants in the interview numbered 6 people, with details 2 editors team and 4 GKPB active congregation in Denpasar City. The results showed Galang Kangin magazine is an internal media among GKPB congregations that convey three values namely, theological values, institutional values of churches and social values that can be positively accepted by GKPB congregation in the city of Denpasar. In line with the development of online cybercommunity media today, publishing Galang Kangin Magazine needs to be published in the form of blog or website so that it can be read by society more broadly. Keywords: Church, Galang Kangin Magazine, Public relations, Value